Lectora Inspire: Boosting environmental awareness with chicken bone cracker e-module - Melly Ismiyaturrohimah; Mustika Nuramalia Handayani; Gilang Garnadi Suryadi (Universitas Pendidikan Indonesia, 2024)
Green skills are skills needed by students to support sustainable development goals. Environmental awareness and innovation skills, which are parts of green skills, have become essential competencies for participants of the Agribusiness in Agricultural Product Processing (APHP). The enhancement of environmental awareness and innovation skills can be achieved through the learning process using instructional media. The instructional media developed in this study is an e-module based on Lectora Inspire. This research aims to determine the suitability of the e-module for chicken bone cracker processing based on Lectora Inspire, to assess the environmental awareness and innovation skills of the learners. The development of this e-module follows the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) and employs a pre-experimental design method with a one-group pretest-posttest design during its implementation. The research findings indicate that the e-module is considered